Parents’ Modeling During the COVID-19 Pandemic: Influences on Family Members’ Diet Quality and Satisfaction With-Food-Related Life in Dual-Earner Parents With Adolescent Children - Schnettler, Berta; Miranda-Zapata, Edgardo; Orellana, Ligia; Saracostti, Mahia; Poblete, Héctor; Lobos, Germán; Adasme-Berríos, Cristian; Lapo, María; Beroiza, Katherine; Grunert, Klaus G. (Frontiers in Nutrition, 2022)
Reciprocal family influences in the food domain have been little explored, particularly during the COVID-19 pandemic. To fill in this gap, this study explored actor and partner effects between parents’ food modeling and parents’ and their adolescent children’s diet quality and satisfaction with food-related life (SWFoL); and the mediating role of diet quality between modeling and SWFoL. This study used a cross-sectional design. A sample of 430 different-sex dual-earner parents and one adolescent child were recruited in Rancagua, Chile, between March and June 2020. Parents answered the modeling dimension of the Comprehensive Feeding Practices Questionnaire. Parents and adolescents answered the Adapted Healthy Eating Index and the Satisfaction with Food-related Life Scale. Analyses were conducted using the Actor-Partner Interdependence Model and structural equation modeling. Results showed that one parent’s modeling enhanced diet quality for themselves, their partner, and the adolescents. Parents’ modeling was associated with their own SWFoL, directly and via their own diet quality. There were positive associations between mothers’ modeling and adolescents’ SWFoL; between mothers’ diet quality and fathers’ SWFoL; and between mothers’ modeling and fathers’ SWFoL via the fathers’ diet quality. Parents’ modeling can improve the three family members’ diet quality, while mothers’ modeling and diet quality showed to improve fathers’ and adolescents’ SWFoL.